TEHNOLOGY AND EQUIPMENT FOR BIOFUEL PRODUCTION FROM RAPESEED OIL - Slusarenko V.V. (Problems of the Regional Energetics)
The paper gives a brief overview of technologies and equipment for the production of biofuel from rapeseed oil - biodiesel. It is presented the description of the processes both cyclical (periodic) nature and processes of continuous production. It is justified the use of the type of the process in dependence of production volume.